The poem “Masa” by César Vallejo from the perspective of the analysis of poetic discourse (Gestionar: revista de empresa y gobierno, 2021)
This article aimed to interpret the mass poem by César Vallejo from the perspective of discourse analysis. The method used was hermeneutics based on phenomenology and structuralism. The technique for obtaining the result was the analysis of the poetic discourse in its textual, enunciative, semiotic, and pragmatic dimensions. The development of the research is reflected in the values of society and the union of human beings.
Keywords: Universal love; analysis; dimensions; semiotics